INFOCOMMUNICATION SUPPORT OF THE ACTORS’ COLLABORATION IN THE INTERSUBJECTIVE MANAGEMENT THEORY - T. V. Moiseeva; N. Yu. Polyaeva (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The theory of intersubjective management, designed to manage social processes in society, is aimed at achieving mutual understanding and consensus among heterogeneous actors united in self-organized communities. Actors who are aware of themselves in a problem situation (rather than just viewing it from the outside) are motivated to solve it, and joint decisions are made by the entire community of actors who are forced to negotiate with each other, realizing that their own resources are not enough to solve the problem. The use of modern information and communication technologies could allow to increase the effectiveness of the decision-making process and reduce its time, providing actors with the means of interacting each other in the process of seeking likeminded people, negotiating and reaching consensus. Therefore, the aim of the research is to find means of infocommunication support for the theory of intersubjective management which help to organize the interaction of actors who found themselves in difficult problem situations in everyday life.Method. The system approach, method of the comparative analysis are applied. For the purpose of better presentation the semantic mean of graphical visualization Free Mind is used.Result. The analysis of modern infocommunication facilities, the most popular among potential actors, is carried out and their comparison is made. The evaluation of the capabilities of all the analyzed means from the point of view of their suitability to the needs of intersubjective management is given. The choice of the most suitable infocommunication facility for use in the company "TBM-Povolzhje" is made.Conclusion. The analysis of infocommunication means allowed to present their wide spectrum for application in practice while using the theory of intersubjective management. The research was performed as part of the state budget theme "Intersubjective Management of Socio-technical Objects Innovative Development with the Use of Situations Ontological Models" (No. AAAA-A16-116040410061-0) of ICCS RAS.